Plasmonic gas sensing in the C+L bands using femtosecond laser inscribed TFBGs - Ioannou, Andreas; Vila, Álvaro Gonzalez; Theodosiou, Antreas; Debliquy, Marc; Kalli, Kyriacos; Caucheteur, Christophe (My University, 2018)
We report femtosecond laser inscribed plane-by-plane tilted Bragg gratings in single-mode photosensitive fiber and their performance as gas sensing device when coated with a thin gold layer. This configuration operates in the C+L bands.
Keywords: Chemical detection; Fiber optic sensors; Gas detectors; Optical fibers